The Influence of Investment and Labor on Economic Growth in South Sumatra Province - Esti Hajiah; Elvira Rosiana; Indri Priscilia; Maya Panorama (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
This research aims to examine the influence of investment and labor on economic growth in South Sumatra Province. The method used in this research uses quantitative methods from cross section data from 17 districts in South Sumatra Province and time series data for 5 years from 2018-2022. Quantitative analysis is processed through the eviews program. Based on the results of the analysis, it was concluded that investment had a partial effect on the economy in South Sumatra Province. The next result was that the labor variable had no partial effect on the economy of South Sumatra Province. Simultaneously, investment and labor have a significant and positive effect on the economic growth of South Sumatra Province.